Transmission of Angiosarcomas From a Common Multiorgan Donor to Four Transplant Recipients. Issue 1 (24th October 2012) - Thoning, J.; Liu, Y.; Bistrup, C.; Thomassen, A.; Borst, C.; Marcussen, N.; Tepel, M.
<x xml:space="preserve">Abstract</x> We describe the donor tumor transmission of metastatic angiosarcomas to four transplant recipients through transplantation of deceased‐donor organs, i.e. kidneys, lung and liver, from an apparently unaffected common female multiorgan donor. Fluorescent in situ hybridization of angiosarcoma cells confirmed that the tumor was of female donor's origin in male kidney recipients. Recent literature associated increased urokinase‐plasminogen‐activator‐receptor (uPAR) and plasma soluble urokinase‐plasminogen‐activator‐receptor (suPAR) levels with metastatic malignancies. Now we found that, compared to baseline levels, both deceased‐donor kidney recipients showed increased uPAR transcripts in mononuclear cells as well as increased plasma suPAR levels after the diagnosis of metastatic angiosarcomas, i.e. 4 months after donor tumor transmission. These results show an association of uPAR/suPAR in donor tumor transmission of metastatic angiosarcomas in humans.